NITROGEN FERTILIZATION AND Azospirillum brasilense INOCULATION ON Panicum maximum CV. Mombasa - Priscila Porfírio Gonçalves (Tropical and Subtropical Agroecosystems, 2020)
Background. Nitrogen fertilization of pastures is considered one of the main limiting factors and that most promote an increase in the production of forage biomass. For this reason, research that evaluates alternative techniques that can complement or supply the demand for N in forage becomes important. Recently, some researches have been studying the action of bacteria like Azospirillum brasilense, and their ability to make symbiotic associations with grasses, fixing atmospheric nitrogen and producing hormones that stimulate the growth of their roots. Objective. The aim of this work was to evaluate the development and production of Panicum maximum cv. Mombasa as a function of nitrogen (N) doses and inoculation with diazotrophic bacteria. Methodology. The experimental design was completely randomized (CRD), in 5 x 2 factorial scheme, in pots with capacity for 10 dm3 of soil, with four replicates. Treatments consisted of the combination of N doses (0, 50, 100, 150, 200 kg ha-1), using urea (45% N) as source, with and without inoculation with Azospirillum brasilense. The parameters evaluated were: SPAD index, leaf dry matter, leaf area, crude protein content (CP), root volume, root dry matter, stem dry matter and leaf/stem ratio. Results. Root volume, CP content, stem dry matter and green color index (SPAD) increased linearly as a function of the N doses. Only leaf/stem ratio and green color index responded to the inoculation with bacteria. Nitrogen fertilization directly contributes to promoting higher yields and fast establishment of the pasture. So, inoculation with Azospirillum brasilense leads to promising results in Panicum maximum cv. Mombasa, improving its leaf/stem ratio and SPAD index. However, it is not sufficient to promote higher forage production, so further research is needed with other grasses to confirm its efficiency, when associated with N. Conclusion. Nitrogen fertilization directly contributes to promoting higher yields and fast establishment of the pasture. Nitrogen doses between 100 and 150 kg ha-1 proved to be the most indicated for the development of P. maximum cv. Mombasa.